iFAST: Building a global financial ecosystem - ABRAHAM, Susheela (Varghese) (Institutional Knowledge at Singapore Management University, 2025)
Launched in 2000, iFAST provided a B2C and B2B online platform offering a suite of investment products and services. In 2022, it acquired a global digital bank in the UK, which fulfilled CEO and co-founder Lim Chung Chun’s long-held vision of iFAST growing into a complete financial ecosystem. In the fourth quarter of 2024, iFAST had generated a total revenue of nearly S$104.14 million, a net profit of S$19.3 million, and offered a total of 25,000 investment products, and had businesses in Singapore, Malaysia, Hong Kong, and China. Much of iFAST’s growth was attributed to the guiding principles of ‘Integrity and Innovation’ established by Chung Chun. The dual principles ensured that the platform was easy to use, time-saving, priced transparently and open to all investors. The principles also produced a company culture that nurtured young, internal talent, that eventually formed a management team that established new regional geographic markets, new businesses, and accepted failures as new opportunities. Although the company had experienced success, its journey had not always run smoothly. Over the years, it faced numerous hurdles relating to country-specific regulations, cultural nuances, and struggled to innovate unique products in competitive markets. Going forward, how could iFAST continue to grow this ecosystem? Could its principles help it develop alternative success strategies for challenging geographies? Additionally, given the company’s rapid growth, Chung Chun would have to be even more deliberate about the way he recruited and nurtured talent. He wondered how he could continue to take iFAST forward, and expand globally in the face of growing industry competition. With this case, students can be taught about the importance of company values in a start-up, producing growth in a new business, expanding regionally, and creating intentional opportunities. The senior management’s strategic choices show how alignment of the core mission and values as demonstrated by key employees, was essential to growth.